Viticultural performance of Cabernet Sauvignon grafted on different rootstocks in high altitude regions of the state of Santa Catarina Desempenho vitivinícola da Cabernet Sauvignon sobre diferentes porta-enxertos em região de altitude de Santa Catarina - Brighenti A.F.* (2011)
Rootstocks are a link between the soil and the canopy; they play an important role in vine adaptation to environmental factors. The objective of this study was to evaluate three rootstocks and two training systems on vineyard productivity, scion growth and fruit physical features. The study was conducted in a experimental vineyard located at the city of Painel (28°01'02"S and 50°08'57"W, altitude 1200 m), in the state of Santa Catarina, Brazil. The cultivar evaluated was the Cabernet Sauvingon grafted on Paulsen 1103 (V. berlandieri × V. rupestris), Couderc 3309 and 101-14 Mgt (V. riparia x V. rupestris), the training systems evaluated were vertical shoot positioning trellis and Y trellis. The plants were five years old and the spacing was 3,0 x 1,5 m. The experiment was evaluated at the seasons 2007/08 and 2008/09. The experimental design was randomized blocks, with four blocks and 20 plants per plot. The variables analysed were leaf area, productivity, Ravaz index, pruning weight, weight and diameter of the berries, cluster weight, number of berries per cluster, soluble solids contents, total acidity, pH, anthocyanins contents, total polyphenols index and tannins. Plants grafted on 1103P presented the lowest productivity and biggest leaf area. The cultivar Couderc 3309 is the less vigorous rootstock, produces heavier berries and interferes positively on fruit set when increases the number of berries per cluster and berry weight. The rootstocks Paulsen 1103 and 101-14 Mgt, presents the best results for total anthocyanins contents.